2021
DOI: 10.1016/j.apsusc.2020.147705
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically-controllable hollow multi-shell magnetite spheres as stable and reusable SERS substrates

Abstract: This study successfully synthesized magnetically-manipulatable and reusable SERS active buoyant substrates, i.e. Ag@SiO 2 @Fe 3 O 4 composite hollow spheres. The composites comprised mesoscopic hollow spheres with a Fe 3 O 4 inner shell of 15-30 nm in thickness and strong ferromagnetism, which were synthesized using spray pyrolysis and the subsequent reduction, and a SiO 2 outer shell to maintain the stability of Fe 3 O 4 , as well as Ag nanoparticles on the sphere surface providing localized surface plasmon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Magnetic SERS substrates have been extensively used for the detection of contaminants because the analytes can be easily separated and enriched from the sample. Further, the SERS intensity can be enhanced with an external magnet. To verify the influence of an external magnetic field, 10 points were randomly selected on the substrate with or without using a magnet. By placing an external magnet under the silicon wafer (Figure c), the FA@ZIF-8 substrate was concentrated in the center of the droplet.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic SERS substrates have been extensively used for the detection of contaminants because the analytes can be easily separated and enriched from the sample. Further, the SERS intensity can be enhanced with an external magnet. To verify the influence of an external magnetic field, 10 points were randomly selected on the substrate with or without using a magnet. By placing an external magnet under the silicon wafer (Figure c), the FA@ZIF-8 substrate was concentrated in the center of the droplet.…”
Section: Resultsmentioning
confidence: 99%
“…The uniformity of SERS signals was approximately 10fold, and the signal intensity was approximately 27-fold higher aer modulating the substrate distribution with magnets, consistent with previous reports. [11][12][13]25 In the absence of magnetic modulation, the widely separated nanoparticles resulted in a scattered and inhomogeneous hotspot distribution. By contrast, the presence of an external magnetic eld decreased the spacing between the FA particles, leading to plasma formation on the surface of the substrate and enhanced electromagnetic elds between the AuNPs.…”
Section: Effect Of An Applied Magnetic Eld On the Sers Signalmentioning
confidence: 99%
“…The ability to reuse magnetic nanoparticles (MNPs) not only promotes economic efficiency but also aligns with ecological sustainability by reducing both costs and the environmental impact. [4][5][6][7][8][9][10][11][12][13][14][15][16] Despite its potential, the practical application of magnetic SERS in realworld scenarios is hampered by a trio of formidable challenges: the inconsistent reproducibility across different batches, concerns over substrate stability, and the inherent nonuniformity of hotspot distribution. 17 To address these issues, recent advances have shied focus toward the integration of plasmonic magnetic nanocomposites with external elds to manipulate hotspot formation and positioning.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of magnetic materials and precious metals Au and Ag, due to their good magnetic properties, can not only achieve rapid separation and easy recycling but also achieve high detection sensitivity. 6 Fan et al 7 reported a magneto-plasmonic Ag−Fe 3 O 4 nanocomposite that could modulate and enhance the SERS activity, but the inhomogeneous distribution of AgNPs resulted in unsatisfactory repeatability and reproducibility of the SERS signal. Han et al 8 prepared recyclable magnetic Fe 3 O 4 @Au core−shell nanocomposites as SERS substrates and used them for thiram detection, but the detection sensitivity was insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is difficult to separate and recycle Au (Ag) from the solution and recycle it. The combination of magnetic materials and precious metals Au and Ag, due to their good magnetic properties, can not only achieve rapid separation and easy recycling but also achieve high detection sensitivity …”
Section: Introductionmentioning
confidence: 99%